Effect of defocusing distance on the forming quality of inner structure parts manufactured via selective laser melting. (June 2022) - Duan, Weipeng; Wu, Meiping; Han, Jitai; Ma, Yiqing; Lu, Peipei; Miao, Xiaojin
A systematical work was studied to illustrate the influence of defocusing distance on the forming quality of inner structure fabricated by selective laser melting for Ti-6Al-4V alloy. The relationship between defocusing distance and dimensional accuracy, surface roughness as well as flatness was investigated, finite element analysis (FEA) was used to show the temperature distribution. The results show that defocusing distance not only had an impact on laser energy density, but also showed a significant influence on the surface pressure of the metal powder. Smaller defocusing distance (0.0 mm) accompanied with higher molten pool maximum temperature (3262.96°C), powder melting and splashing at the same time. On the contrary, larger defocusing distance leading to unmelted powder and powder bonding, which influences the forming quality of samples. Dimensional accuracy was less affected in 0.0, 1.0, 2.0 mm defocusing distance (5%), but changed dramatically when it is 3.0 mm (22%). In the same condition, similar variation trend of surface roughness (Ra) and flatness was observed, and varying from 5.1 to 27.3 μm and 0.05 to 0.26 mm, respectively. Simultaneously, the bottom surface is less affected, while the other three sides have the opposite situation. Pores and unmelted powder can be seen on the surface, it is the comprehensive effect of laser energy density and surface pressure. It proves that it is feasible to manufacture inner structure by controlling this process parameter during SLM process, the influence mechanism of defocusing distance on forming quality was also illustrated in this work.